Mengembangkan Strategi Bisnis di Era Society 4.0 melalui Pelatihan Business Model Canvas, Strategi Co-Branding, Selling Skill, dan Digital Marketing untuk Mahasiswa di Indonesia - Wilyan Adiasari; Carola Basuki; Anton Kurniawan; Hasna Larasati (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
Along with the development of the era and increasingly rapid technology today, it triggers every business player to create more value in their business. Moreover, there are many competitors who are one of the business threats that need to be faced. Therefore, to meet current market needs, there needs to be aware about how to apply suitable strategies for business. More over early business owner need to have more understanding about business model canvas, cobranding strategy, selling skills, and digital marketing application. The Ayo Kreasi Community is a forum and space for the young generation of future leaders, collaboration media, connections and synergies in developing solutions, creations and innovations based on student talent development to create a superior generation of character and benefit for the homeland and nation starting from the Higher Education Environment. Therefore, the provision of material regarding the business strategies is able to become an additional knowledge for students that can be directly implemented to create positive collaborations for work